Rapid Screening of Berseem Clover (Trifolium alexandrinum) Endophytic Bacteria for Rice Plant Seedlings Growth-Promoting Agents. (19th June 2013) - Etesami, H.; Mirsyedhosseini, H.; Alikhani, H. A.
Abstract : A simple screening method to detect berseem clover ( Trifolium alexandrinum ) endophytic bacteria for rice plant growth-promoting agents on the basis of a root colonization bioassay and a plant growth promoting trait is characterized. Firstly, 200 isolates (80 endophytes and 120 rhizospheric isolates) isolated from berseem clover were inoculated as 10 mixtures of 20 strains each on two rice varieties under gnotobiotic conditions. Then, the reisolated endophytic strains from two rice varieties were characterized for plant growth promoting (PGP) traits. Secondly, the colonization and growth promoting effects of endophytic strains were compared in inoculated rice plantlets as single-strain inoculants. A significant relationship among indole-3-acetic acid (IAA) producing isolates, the size of root colonization, and plant growth was observed. Our results suggest that the ability of IAA production by the endophytic bacteria which may have a stimulatory effect on plant development may be the first plant growth promoting trait for screening bacteria isolated from clover plant for rice plant growth promoting agents. In addition, this study indicates that the selected bacterial isolates based on their IAA producing trait have the potential for PGP and more colonization of rice plant.